Modifikasi Lahan Pekarangan Non Produktif Menjadi Sumber Ketahanan Pangan Dan Ekonomi Keluarga - Fitri Kurniawati; Anzori Anzori; Silke Sachanovrissa; Kresnawati Kresnawati; Yudi Irawan Abi (Jurnal Dehasen Untuk Negeri, 2023)
Currently the use of yards is an alternative for the community to meet the needs of the family. Because the yard has the potential to provide food for the family, the narrow plot of land can be modified into a yard that produces usability such as growing vegetables, empon-empon and fruits. Modification of narrow land can use several planting techniques, namely plants using pots (polybags) and hydroponics. The activity was carried out at the Pematang Indah Estate Housing Complex, Pematang Village, the Governor of Muara Bangkahulu District, Bengkulu City. The method of this activity is carried out by way of socialization through lectures and question and answer discussions with housewives who are formed in arisan groups. It is hoped that with this socialization there will be a maximum change in the function of the yard, the community already understands the importance of diversifying food and the health of the food consumed, and understands the management of family income by selling vegetable crops.